The Errors In Writing Hamzah: What Should Students Do?/ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙÙŠ ÙƒØªØ§Ø¨Ø© Ø§Ù„Ù‡Ù…Ø²Ø© : Ù…Ø§Ø°Ø§ ÙŠÙØ¹Ù„ Ø§Ù„Ø·Ù„Ø§Ø¨ØŸ - Pimada, Luluk Humairo; Amrulloh, Muhammad Afif; Zahra, Dwi Noviatul; Syahid, Ahmad Habibi (Ijaz Arabi Journal of Arabic Learning, 2021)
Arabic is a second language for some Indonesian students, but in reality, there are still many errors in writing. Especially in the writing of the Hamza letters that have not been mastered properly. Therefore this research was conducted to know the forms of errors in writing Hamza, the causes of errors in writing, and the strategies used to minimize errors in writing Arabic. This study took the first-level learning at the Arabic Language Education Department at IAIN Samarinda as a sample. This research is a qualitative descriptive study. Data collection using observation and documentation. Data were analyzed using Miles and Huberman's theory through data collection processing, data reduction, data presentation, and concluding. The mistakes that often occur in writing the letters Hamza based on their type are Hamzah Qaá¹'i, Hamzah Waá¹£l, Hamzah Mutawaá¹£iá¹ah, and Hamzah Mutaá¹arifah. These errors are based on the lack of knowledge of Arabic writing rules, lack of practice as a form of Arabic writing practice. Meanwhile, the strategy used to minimize these errors is to use a variety of methods in teaching Arabic, also to apply the rules of Imla ', utilize media or multimedia learning, and apply the theory of writing skills gradually. Then give examples of various Arabic writing models, and increase Arabic writing exercises accompanied by proper Arabic writing rules.